Possible internal viral shedding and interferon production after clinical recovery from COVID-19: Case report - Ito, Asuka; Okada, Takayuki; Minato, Naoki; Hattori, Fumiyuki (Frontiers in Medicine, 2022)
A 70-year-old man underwent off-pump coronary artery bypass grafting 28 days after his recovery from coronavirus disease 2019 (COVID-19), which was confirmed by a negative polymerase chain reaction (PCR) test result for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from a nasopharyngeal swab. The PCR test result was also negative for nasopharyngeal sampling 5 days prior to the surgery. However, his redundant saphenous vein and sputum through the endotracheal tube that were taken on the operative day showed the presence of SARS-CoV-2 by PCR. Immunohistochemical analysis of Spike and Nucleoprotein of the saphenous vein showed small clusters of each antigen-positive speckle. Ultrastructural imaging of the saphenous vein showed virus-like particles. The cell-based assay suggested that the patient’s serum contained a higher concentration of type-I interferons than that of healthy control sera. These observations suggest that internal viral shedding and, to some extent, innate immune responses continue after COVID-19 recovery.